1986
DOI: 10.1111/j.1745-6606.1986.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Local Consumer Information Systems for Services: A Test

Abstract: This paper reports on a survey of consumers' experiences with local services firms that was conducted by the Montgomery County, Maryland Office of Consumer Affairs and supported by an FTC grant. Over 1,200 individuals evaluated auto repair, heating and air conditioning, home remodeling, roofing, and insulation contracting firms on three dimensions: satisfaction with work performed, price in relation to quality, and strength of recommendation. Results for the heating and air conditioning category were published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Restaurants can act on diners’ altruism and willingness to give back to the local community. Research has shown that 72% of consumers who were asked to write a review for a local business went on to do so (Murphy, 2020). Therefore, businesses can explicitly seek support and ask guests to review their business.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Restaurants can act on diners’ altruism and willingness to give back to the local community. Research has shown that 72% of consumers who were asked to write a review for a local business went on to do so (Murphy, 2020). Therefore, businesses can explicitly seek support and ask guests to review their business.…”
Section: Discussionmentioning
confidence: 99%
“…The enormous pressure caused by the crisis has crushed small independent businesses, which are often viewed as the lifeblood of the economy. In the year 2020, there were more positive than negative reviews posted by restaurant customers (Murphy, 2020). Although the road to a complete recovery remains rocky, consumer enthusiasm to support local communities is worthy of being shared with a broader audience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study makes it easier to comprehend the qualities of assessments that encourage wise decisionmaking, and this holds true for both employees and managers inside a company. In addition, a Bright Local Survey (Murphy, 2019) found that 82% of potential employees examine online firm ratings on employer review sites. It is reasonable to speculate that this event affects the standing of the business.…”
Section: Journal Of Business Researchmentioning
confidence: 99%
“…, 2019). In fact, 97% of customers rely on online reviews and 85% of customers perceive those reviews as personal recommendations (Murphy, 2017). Customers are even willing to pay at least 20% more for products or services with a 5-star rating vis-à-vis those with a 4-star rating (Cheung and Lee, 2012).…”
Section: Introductionmentioning
confidence: 99%